The politics of sacred places: a view from Israel-Palestine - Luz, Nimrod (Bloomsbury studies in religion, space and place, 2025)
"The Politics of Sacred Places is a study of the socio-political dimensions of sacred sites in Israel Palestine, drawing on over 20 years of in-depth ethnographic research which introduces cutting-edge theories on secularization, struggles for recognition, and diversity issues. This book focuses on contemporary sacred sites and their socio-political meanings for minorities within a hegemonic and a secularizing state-system. It argues that sacred places provide a space that is less scrutinized by the state and where alternative visions of the socio-political may be produced. A plethora of sites and case studies are examined, including the rural shrine of Maqam abu al-Hijja in the lower Galilee, the Mosque of Hassan Bek in the heart of Tel Aviv-Jaffa and the most disputed sacred place in the region, the Haram al-Sharif in Jerusalem. These sites are explored through mostly a phenomenological lens and in various contexts, from the individual body to the global. This book offers a critical-analytical study of the socio-political aspects of sacred sites in contemporary societies within the broader understanding of scale and the spatial turn in the study of religion"--